The role of e-government in increasing transparency and accountability of public administration in the digital era - Setyarto, Dwiatmodjo Budi; Alimuddin, Alimuddin; Mulyaningsih, Mulyaningsih; Judijanto, Loso (Edelweiss Applied Science and Technology, 2025)
This research aims to explore the role of e-government in increasing transparency and accountability in public administration in the digital era. As digital technology develops, governments around the world are increasingly adopting e-government solutions to improve public services, strengthen public trust, and simplify administrative processes. This study investigates how the integration of information and communication technology (ICT) in public administration can drive greater transparency and accountability, which are essential elements of good governance. A mixed-methods approach is used to provide a comprehensive understanding of the impact of e-government initiatives. The qualitative component involves in-depth interviews with government officials, policymakers, and e-government project leaders in various sectors to understand the challenges and successes in the implementation of digital government solutions. The quantitative aspect uses a survey of 500 public sector employees and citizens in countries with advanced e-government systems to assess perceptions regarding transparency and accountability in digital services. The study found that the implementation of e-government platforms has brought significant improvements in transparency, with 70% of respondents reporting better access to public information and government data. In addition, accountability has been strengthened as digital platforms facilitate more efficient monitoring and auditing of public sector activities. However, challenges such as the digital literacy gap, concerns about data security, and the digital divide are identified as barriers to maximizing the potential of e-government. The study concludes that e-government plays an important role in improving transparency and accountability in public administration by enabling better access to information and facilitating a more transparent decision-making process. The study recommends further investments in digital infrastructure, capacity building for government officials, and public education to address existing challenges. These findings emphasize the importance of digital inclusivity and the need for a comprehensive strategy to ensure equal access to e-government services across all segments of society.